2006
DOI: 10.1073/pnas.0607012103
|View full text |Cite
|
Sign up to set email alerts
|

Correction of hemophilia as a proof of concept for treatment of monogenic diseases by fetal spleen transplantation

Abstract: Previous clinical attempts to correct genetic deficiencies such as hemophilia or Gaucher disease by transplantation of allogeneic spleen were associated with aggressive graft versus host disease, mediated by mature T cells derived from the donor spleen. We show that a fetal pig spleen harvested at the embryonic day 42 stage, before the appearance of T cells, exhibited optimal growth potential upon transplantation into SCID mice, and the growing tissue expressed factor VIII. Transplantation of embryonic day 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
3
23
0
1
Order By: Relevance
“…Recent studies using a cell therapy approach 8,9 or cell typespecific knockout experiments indicated that FVIII is produced largely in liver sinusoidal endothelial cells (LSEC); 10,11 although FVIII mRNA was present in endothelial cells of kidneys, spleen and lungs, it was absent in endothelial cells of the brain and heart. 10,[12][13][14][15] These findings were in agreement with studies showing that hemophilic patients benefited from transplantation of the spleen in the long-term. 16,17 On the other hand, early studies in hemophilic dogs did not show longterm correction and other reports described the spleen as only a store for FVIII-expressing cells.…”
Section: Introductionsupporting
confidence: 81%
“…Recent studies using a cell therapy approach 8,9 or cell typespecific knockout experiments indicated that FVIII is produced largely in liver sinusoidal endothelial cells (LSEC); 10,11 although FVIII mRNA was present in endothelial cells of kidneys, spleen and lungs, it was absent in endothelial cells of the brain and heart. 10,[12][13][14][15] These findings were in agreement with studies showing that hemophilic patients benefited from transplantation of the spleen in the long-term. 16,17 On the other hand, early studies in hemophilic dogs did not show longterm correction and other reports described the spleen as only a store for FVIII-expressing cells.…”
Section: Introductionsupporting
confidence: 81%
“…5,6 Nonetheless, extrahepatic organs probably contributed in FVIII production, as indicated by FVIII synthesis in spleen, lungs, or pancreatic islets. [6][7][8] This was in agreement with lack of plasma FVIII deficiency after OLT with donor liver from dogs or people with hemophilia A because such donor liver cells would not have synthesized or secreted FVIII. 9,10 Therefore, whether nonendothelial cells, and cells in extrahepatic organs, could also produce FVIII was not excluded.…”
Section: Introductionsupporting
confidence: 62%
“…The ability of endothelial cells in liver and other organs, as well as of nonhepatic cell types, to produce FVIII offer frameworks for understanding alterations in FVIII levels during diseases. 47 Similarly, transplantation studies showing efficacy of dissociated spleen cells or splenic tissue in people with hemophilia should be accounted for by FVIII production in monocytes, besides endothelial cells, 7,48,49 because the spleen is a major reservoir of MNCs and macrophages. 50 After splenic cell transplants, plasma FVIII activity levels peaked in 4 to 7 days, 48 which was in agreement with our studies of KCs and MSCs transplants, which showed control of bleeding after 3 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy is based on the growing evidence, over the past 5 decades, demonstrating maternal immune tolerance to the fetus (2,3), and on recent observations that embryonic tissues exhibit reduced immunogenicity in various transplantation settings (4)(5)(6)(7). Considering that very early embryonic tissues are associated with a substantial risk of teratoma formation, we have attempted, during the past several years, to define the earliest gestational time point that does not pose a teratoma risk for transplantation of different embryonic pig tissues, including kidney (6), heart (unpublished), spleen (8), pancreas, liver, and lung (7) into SCID mice. Once this threshold was established, we were able to further characterize an optimal gestational window for transplantation based on growth potential and immunogenicity.…”
mentioning
confidence: 99%